MODEL JENJANG KARIR JABATAN LEVEL ADMINISTRATOR DAN PENGAWAS (ESELON III DAN IV) BERBASIS KOMPETENSI DI LINGKUNGAN SETDA PROVINSI GORONTALO - Irfan Ibrahim (Universitas Muhammadiyah Gorontalo, 2015)
This study aims to determine the use of career path positions, measuring the job competency requirements and design a career path position as a competence-based simulation. This study uses a case study of exploratory design, while the type of research is descriptive qualitative data sources upon 40 structural officials and documents in Gorontalo Provincial Secretariat. While data collection techniques used is through questionnaires and documentation. Data analysis technique used was cluster analysis that aims to get a group position based on proximity/similarity of competence between the positions of the other positions. Results of cluster analysis showed that the group was formed consisting of 12 clusters and 4 (four) family positions, in which positions within a job family can be rotated and promoted directly, while outside the office of the family done by cross posting. Thus it can be conducted to determine the standard of job competency requirements and design of a competency-based career path positions in the Secretariat of Gorontalo Province. The result is expected to be a reference in an attempt to fix the career management, which in its implementation requires some pre-conditions, actions of socialization and followed by other elements of career management.